A participação popular em Campina do Monte Alegre (SP): entre as festas de São Roque, do milho e o associativismo - Fujita, Raquel Peres Pereira (Universidade Federal de São Carlos, 2023)
This work analyzes mass participation of the people from Campina do Monte Alegre in the political and socio-cultural field. The main purpose of the studies was to cognize and understand the type of participation in that society, as well as its deployment, observing how the dwellers understand the meaning of mass participation, and how they perform it on a daily basis. The methodology used consisted of literature review and interviews with some residents based on a semi-structured questionnaire, done and applied by the researcher. The information collected were qualitatively analyzed. The people’s participation have already occurred in Campina do Monte Alegre (SP). As an example, the religious festivities, even before being a constitutional right, granted by the 1988 letter and, more recently, the presence of associativism is observed. All of these were of great importance for the city formation, which was emancipated in 1999. Therefore, this is a text in which the researcher, who is also a resident from the referred city, shows that there are lots of peculiarities yet to be solved, so that the awareness regarding the right to mass participation may be extended to all local citizens. Besides poiting out to possible demonstrations of resurgence in participatory life through cooperation initiatives and partnership between small farmers from the city and são carlos federal university, Lagoa do Sino campus.
Popular participation in Campina do Monte Alegre (SP): between São Roque, corn festivals and associations
Keywords: Campina do Monte Alegre (SP); Participação Popular; Festas Populares; Associativismo; People’s Participation; Popular Festivities; Associativism; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL